Formulation Setting Of Settlement Of Authority Disputes Between State’s Instituti0n Are Not Subject To The Constitution Of The Republic Of Indonesia Year 1945 - Yulianto, Winasis (International Journal of Educational Research & Social Sciences, 2022)
The provisions of Article 24C paragraph (1) of the Republic of Indonesia Constitution Year 1945 give authority to the Constitutional Court to the dispute over the authority of state institutions whose authority is granted by the Constitution. Whereas disputes between state institutions that are not regulated in the Republic of Indonesia Constitution Year 1945 have a vacuum of norm.The results of the study show that: first, the need to regulate disputes over authority between state institutions that are not regulated in the Republic of Indonesia Constitution Year 1945 because Indonesia is a constitutional state, due to the incomplete discussion in the Amendment of the Republic of Indonesia Constitution Year 1945, due to the potential for disputes of authority between state institutions. Second, the legal implications of the settlement of authority between state institutions not regulated in the Republic of Indonesia Constitution Year 1945 conducted by the President through instructions for resolving disputes. Third, in the perspective of state life, the formulation of disputes settlement arrangements between state institutions can be done through three options: (1) expanding the authority of the Constitutional Court (2) expanding the authority of the Supreme Court (3) giving authority to other state institutions.